The effects of positive thinking education for adolescent girls on their conflicts with their mothers: A randomized controlled trial - Fatemeh Nematian; Zahra Tagharrobi; Zahra Sooki; Khadijeh Sharifi (Kashan University of Medical Sciences, 2022)
Background: Adolescent-parent conflict (APC) has damaging effects on both adolescents and parents and hence effective strategies for its management are necessary. Objectives: The aim of this study was to evaluate the effects of positive thinking (PT) education for adolescent girls on their conflicts with their mothers. Methods: This randomized controlled trial was conducted in 2019-2020. Participants were 48 adolescent girls conveniently selected from two high schools in Kashan, Iran, and randomly allocated to a control and an intervention group through block randomization. Participants in the intervention group received PT education in eight 90 min sessions held twice weekly. A demographic questionnaire and the APC questionnaire were used for data collection. Data were analyzed through the Chi-square, Fisher's exact test, independent-sample t-tests, and the repeated measures analysis of variance. Results: There was no significant difference between the intervention and the control groups respecting the pretest mean scores of APC frequency (244.250 ± 43.353 vs. 234.042 ± 36.218) and APC intensity (24.665 ± 14.244 vs. 27.220 ± 21.829). However, the mean scores of APC frequency and intensity in the intervention group were significantly less than the control group at the end of the study intervention (155.625 ± 28.740 vs. 240.458 ± 35.234 and 13.248 ± 10.660 vs. 35.670 ± 18.998) and 1 month later (122.708 ± 12.302 vs. 241.958 ± 34.719 and 9.693 ± 7.040 vs. 40.258 ± 19.001) (P < 0.05). Conclusion: Group PT education significantly reduces APC. Nurses, midwives, and mental health specialists can use PT education to reduce APC and improve the mental health of communities.